Android-Based Adolescent Reproductive Health Application (Kepo Remaja) as an Educational Media for Preventing Early-Age Pregnancy - Erlin Kiriwenno (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2026)
Adolescent pregnancy is a reproductive health issue in many countries, including Indonesia, and poses risks to both mother and baby. Early-age pregnancy increases health complications, highlighting the need for prevention through reproductive health education and improved access to adolescent-friendly services. This study aimed to develop an Android-based application, “Kepo Remaja,” as an educational tool to prevent adolescent pregnancy. The study used a Research and Development (R&D) design with the ADDIE model and was conducted in Central Maluku, Indonesia, involving adolescent students and health workers as prospective users. Validation involved five material experts and two media experts. A needs analysis identified key features, including assessment, health monitoring, consultation services, and educational materials. The application was developed and evaluated by experts. Qualitative data were analyzed thematically, while quantitative data were analyzed using descriptive statistics with a Likert scale. Results showed that material experts rated 94.26% and media experts 94.31%, both categorized as excellent. In conclusion, the Kepo Remaja application is user-friendly, engaging, and feasible as an educational medium, with potential to support adolescent reproductive health programs and assist students, health workers, and policymakers in preventing adolescent pregnancy.